Cognition and influencing factors of secondary prevention in patients with ischemic stroke 1 year after discharge in Southwest China: a cross-sectional survey - Zhong, Xuemin; Li, Li; Ye, Qing; Wang, Jian; He, Lanying; Li, Changqing (Frontiers in Neurology, 2025)
Although the risk of recurrent stroke is very high in patients with ischemic stroke (IS), the implementation of secondary prevention of IS has not received enough attention. Therefore, we aimed to investigate the cognition and compliance status of secondary prevention in patients with IS in southwest China and explore the factors affecting compliance with secondary prevention 1 year after discharge. We conducted a cross-sectional survey of patients with IS 1 year after discharge in southwest China through convenience sampling. Factors affecting the compliance of secondary prevention in patients with IS after discharge were analysed. A total of 1,041 patients were included in our study. Nearly one-third of patients did not follow secondary prevention measures according to the guidelines, and an improvement in lifestyle was even less likely. Living with or without children did not significantly affect patient compliance (odds ratio 1.11; 95% confidence interval 0.83–1.49; p = 0.47). Furthermore, no significant differences were observed in the probability of treatment acceptance between patients experiencing one or two of the following conditions: hypertension, diabetes, and hyperlipidemia, and those with all three conditions. Thus, patients with IS have insufficient compliance with secondary prevention and there is a particular lack of emphasis on lifestyle improvement. Further interventions are needed to improve compliance with secondary prevention in patients with IS, especially patients with all three conditions of hypertension, diabetes, and hyperlipidemia.